Amazing mysteries - Everett, Bill 1917-1973 (Fantagraphics Books, 2011)
This book collects over 200 pages of this never-before-reprinted work from titles such as Amazing Mystery Funnies (1938), Amazing-Man Comics (1939), Target Comics (1940), Heroic Comics (1940), and Blue Bolt Comics (1940). These titles feature an endless array of great vintage Everett characters such as Amazing-Man, Hydroman, Skyrocket Steele, Sub-Zero, The Chameleon, and many more, all produced by Everetts shop Funnies, Inc. for such clients as Centaur, Novelty Press, and Eastern Color, and all displaying Everetts brilliant cartooning and energetic storytelling
Keywords: Comics (Graphic works); Underground comics; Superheroes -- Comic books, strips, etc; Comic